2000
DOI: 10.1016/s0886-3350(99)00417-4
|View full text |Cite
|
Sign up to set email alerts
|

Phakic posterior chamber lenses for high myopia: Functional and anatomical outcomes

Abstract: Implantation of posterior chamber phakic IOLs is effective and predictable; however, long-term follow-up is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(39 citation statements)
references
References 11 publications
4
33
1
1
Order By: Relevance
“…though the incidence appears lower with use of the V4 model of ICL. 17 In our series, the incidence was higher References than noted in another study, 15 …”
Section: Anatomical Outcomecontrasting
confidence: 41%
“…though the incidence appears lower with use of the V4 model of ICL. 17 In our series, the incidence was higher References than noted in another study, 15 …”
Section: Anatomical Outcomecontrasting
confidence: 41%
“…These results are even better compared with those of other posterior chamber lenses. [18][19][20][21][22] Few short-term complications were observed, such as IOP increase during the first postoperative day because of residual viscoelastic 23 and during the first month because of corticosteroid response. Corticosteroids were used to prevent postsurgery inflammation, but it might instead to avoid this steroid side effect.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is not always a correspondence between white-to-white and sulcus-to-sulcus, and indeed, it differs greatly between individuals. If a large-diameter lens is inserted, crystalline lens opacification tends not to occur [10], and did not occur with our 13.5-mm lens, but IOP elevation and effects on corneal endothelial cells remain a concern [2].…”
Section: Discussionmentioning
confidence: 76%
“…In Japan, a clinical trial of ICL (Staar Surgical, USA), a posterior chamber type of phakic IOL that can be inserted through a small corneal incision of 3.2 mm using an injector, was started in 2003. The currently anticipated problems include intraoperative crystalline lens damage [2,15], and, as postoperative complications, glaucoma [1,2,11,22], loss of corneal endothelial cells [2,6,7,22] and secondary cataract [4,10,11,15,22,24]. A trial of ICL in the USA showed a 2.1% incidence of secondary cataract [22].…”
Section: Introductionmentioning
confidence: 99%